The Case for Rate Hikes: Did the Fed Prematurely Raise Rates? - L. Randall Wray (Levy Economics Institute of Bard College, 2004)
For a time, the Federal Open Market Committee (FOMC) seemed to have learned from the mistakes of the past. Instead of taking good economic performance as a sign of incipient inflation, Chairman Alan Greenspan kept interest rates relatively low in the late 1990s, even as unemployment plummeted. Many commentators worried that the FOMC's unusually easy stance would usher in a period of runaway inflation, but inflation stayed in the 2 to 3 percent range. Now, with scant evidence of an inflationary threat, Greenspan and his committee seem intent on raising interest rates. Greenspan argues that the current anemic expansion is self-sustaining and no longer needs the support of low interest rates. In this new brief, Levy Institute Senior Scholar L. Randall Wray evaluates the Fed's concern about a coming inflation and its decision to begin raising interest rates. He begins with an examination of key market developments that might signal inflation. Most economists worry about inflation when labor markets begin to tighten and employees gain the bargaining power necessary to demand pay raises. Wray marshals an array of evidence demonstrating that workers can only wish for such conditions. The economy has created no net new jobs since the beginning of the current presidential term. To match the 64.4 percent proportion of adults who held jobs during the Clinton era, the economy would have to generate four million new positions. It is clear that the job market will not be a source of inflation any more than it was during the Clinton boom.
Keywords: 330; Geldpolitik; Zinspolitik; Geldpolitisches Ziel; Konjunkturpolitik; USA